KEBUTUHAN FASILITAS PENYEBERANG JALAN DENGAN METODE GAP KRITIS (Studi Kasus Jalan Raya Semarang – Kendal Km. 16.50) - Y.I. Wicaksono; Joko Siswanto (Diponegoro University, 2011)
This study want to measure the performance of pedestrian facilities ( zebra cross), particularly the critical gapanalysis to see the level of opportunity to cross the street safely. To support the recommendations that will be setin addition to the critical gap method will be investigated also waiting time and total time to cross the street andanalysis of types of facilities based on the volume of pedestrian and vehicle volume as the raw determination ofthe crossing facility.From some discussion can be summarized that according to the study analyzes the volume of pedestrian andvehicle volumes obtained by the recommended pedestrian facilities according to standard determination of thecrossing facility is the type of pelican crossing with a separator. Based on the analysis of waiting time to crossthe street, 93% require pedestrian waiting time, with the average waiting time to cross and the total time tocross at that location, which is 56.61 seconds and 79.25 seconds. The condition is very far from the pedestrianshould not waiting more than 30 seconds.Results of analysis of critical gaps, both based on the critical gap only in the morning or combined critical gapin the morning and afternoon shows very little chance of crossing the road owned by the defector, on themorning of 7 times for critical gap in only the morning and 11 times for a combination of critical gap Total 125waders for 06.30 until 7:30 pm, and 20 times based on a critical gap only in the morning a and 29 times forcritical gap combination of pedestrian total of 66 people over at 07.30 until 08:30 pm.Thus based on the results of some analysis that has been done can be concluded that pedestrian facilities are noteffectively to use zebra cross type . The proposed type of road crossing facilities on arterial roads for thepedestrian to use a pedestrian facility type like overpass or underpass to eliminate conflicts between thevehicle flow and a pedestrian crossing.